2018
DOI: 10.1080/09544828.2018.1436162
|View full text |Cite
|
Sign up to set email alerts
|

Educating for a systems design approach to complex societal problems

Abstract: Design education has devoted little attention to the topic of societal systems transformation in the context of sustainable development. This paper reports on a master's-level course that aims to build the capacity for design engineering students to adopt a Systems Design Approach comprised of the integration of Product-Service System (PSS) and Systems Thinking, in order to develop sustainable energy systems concepts. We identify key factors for skilful performance when designing solutions for complex societal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Based on Costa Junior et al. (2018), the authors suggest five key systems-oriented skills necessary for skilful performance when tackling complex societal systems or problems (see Table 4).…”
Section: Results: Conceptual Framework For Systems Design Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Costa Junior et al. (2018), the authors suggest five key systems-oriented skills necessary for skilful performance when tackling complex societal systems or problems (see Table 4).…”
Section: Results: Conceptual Framework For Systems Design Approachmentioning
confidence: 99%
“…Nevertheless, they are problems that impact everyday life, as is the case with sustainability issues in developing countries (DeTombe 2013, 2015 a ). For example, the complex societal problem of providing access to affordable, reliable, and sustainable energy in low-income households is hard to define, describe, and structure based on the available resources, infrastructure, and demand (see Costa Junior, Diehl & Secomandi 2018).…”
Section: Uncovering the Foundations Of A Systems Design Approach: Selmentioning
confidence: 99%
“…In sum, from a theoretical standpoint, four elements of design, along with the participatory notion of design, have certain advantages for constructing a network of actors. In particular, through value co-creation (i.e., from highly fundamental to pragmatic and relational methods), design can create a unique condition for transcending a current situation into a desirable future from which knowledge and experiences can be created through the relations between actors [23,143]. In this case, the integration of the aforementioned aspects of design (fundamental, pragmatic, reflective, and kaleidoscopic notions of design), along with the design tendency to empower actors to co-create value in a complex context, has a great capacity to construct controversies in a social system [109,117,131].…”
Section: Discussionmentioning
confidence: 99%
“…Sangiorgi and Junginger [117] (p. 165) confirmed that the study of "service implementation not only relates to academic frameworks, definitions, and fundamental procedures but also to how it influences businesses and society". Similarly, Costa Junior and Diehl [118] revealed that a design approach in design education needs to adopt sustainable product service systems to solve complex social problems. PSS inherently considers sustainability, as shown by these studies.…”
Section: How Does Service Design Better Facilitate Sustainability Con...mentioning
confidence: 99%